(untitled) - McGrath, Alister E.; (1953-...) (U.S.A., 1990)
Alister E. McGrath begins his book by critically engaging the views of George Lindbeck on doctrine before moving on to present a fresh understanding of the nature and function of Christian doctrine within the church. Particular attention is paid to the way in which doctrine acts as a demarcator between communities of faith, providing important insights into contemporary ecumenical debates. McGrath also explores the crucial issue of the authority of the past in Christian theology, focusing especially on how doctrine serves to maintain continuity within the Christian tradition. The Genesis of Doctrine represents an exploration of a `middle way` in relation to the significance of Christian doctrine, rejecting both those approaches that insist on the uncritical repetition of the doctrinal heritage of the past and those that disallow the authority of past doctrinal formulations. The book concludes by considering whether doctrine has a future within the church, answering this question in the affirmative on the basis of a number of important theological and cultural considerations.
Keywords: Authority -- Religious aspects